Application of Artificial Intelligence in Motivating Court Decisions: Legal Basis and Foreign Experience - Leheza, Yevhen; Yankovyi , Mykola; Medvedenko, Nadiia; Vaida, Taras; Koval, Marat (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
The article is devoted to the study of opportunities and challenges of using artificial intelligence in motivating court decisions.Â An important aspect of this process consists of the application of special knowledge by judges in the context of analyzing evidence and legal evaluation of this evidence. The use of artificial intelligence in this area can become a significant innovation that can improve the quality of court decisions and ensure objectivity in the sphere of justice. Artificial intelligence technologies are rapidly developing, and their potential application in the sphere of judiciary has become a subject of deep interest both among the scientific community and among representatives of legal professions. According to the research results, it has been established that the application of artificial intelligence during the motivation of court decisions is possible provided the development and implementation of effective legal mechanisms that will allow coordination and regulation of the specified process. Also, the procedure of implementing relevant changes in the justice system of Ukraine should take place with the use of a balanced and scientifically based approach, which allows for weighing potential risks and benefits and developing recommendations for the proper practical and ethical use of artificial intelligence technologies.